Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material with high energy storage density under low electric field and preparation method of Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material

By using composite ion doping of Nd/Ce/Co/Al/Mn-doped BSBNT-based ceramic materials and a two-step sintering method, the problems of high energy density and dielectric stability of sodium bismuth titanate-based dielectric ceramics under low electric fields were solved, achieving efficient energy storage performance and stability, suitable for microelectronic devices.

CN121377757APending Publication Date: 2026-01-23JINGDEZHEN CERAMIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511507846.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing sodium bismuth titanate-based dielectric ceramic materials suffer from the risk of electrical breakdown under high electric fields and unstable dielectric properties in terms of high energy density. They are difficult to achieve a synergy between high saturation polarization and low remanent polarization under low electric fields, and their temperature stability and frequency stability are insufficient, which limits their application in microelectronic devices.

Method used

By replacing A-site ions with Nd3+/Ce4+ composite high-valence ions and replacing B-site ions with Co2+/Al3+/Mn4+ composite low-valence ions, combined with a two-step sintering method, the grain growth behavior is controlled to form a multi-level domain structure, thereby improving the polarization intensity and dielectric stability of the material.

Benefits of technology

Achieving high energy storage density under low electric fields improves the temperature, frequency, and fatigue stability of materials, meeting the application requirements of microelectronic devices, while also being environmentally friendly and having low production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121377757A_ABST
    Figure CN121377757A_ABST
Patent Text Reader

Abstract

The invention discloses an Nd / Ce / Co / Al / Mn doped BSBNT-based ceramic material with high energy storage density under a low electric field and a preparation method thereof, aiming at Bi < 3 + >, Na < + >, Ba < 2 + > and Sr < 2 + > ions at the A site of a (Bi0. 5Na0. 5) 0.6 (Ba0. 3Sr0. 7) 0.4 TiO3 ceramic material, composite high-valence ions [Nd0. 8Ce0. 2] 3.2 < + > formed by Nd < 3 + > and Ce < 4 + > with coordination of 12 are used for doping and substitution, aiming at Ti < 4 + > ions at the B site, composite low-valence ions [Co0. 2Al0. 5Mn0. 3] 3.1 < + > formed by Co < 2 + >, Al < 3 + > and Mn < 4 + Through the composite doping modification, the dielectric temperature stability is improved while the high Pmax is maintained, the Pr is reduced and the effective energy storage density of a unit electric field is improved, so that a novel environment-friendly energy storage ceramic material with excellent comprehensive electrical properties under a low electric field is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lead-free dielectric energy storage ceramic materials technology, and in particular to a composite ion-doped enhanced sodium titanate dielectric energy storage ceramic material with high energy storage density under low electric field and its preparation method. Background Technology

[0002] Dielectric capacitors have significant advantages such as high power density (~GW / kg), fast charge / discharge speed (microseconds, even nanoseconds), wide operating temperature range, and long service life, making them the preferred material for pulse power energy storage applications. Among them, novel relaxor ferroelectric ceramics and antiferroelectric ceramics are particularly favored due to their high energy density (~GW / kg). W rec >6 J / cm 3 It has attracted much attention, but the prerequisite for achieving high energy storage density is to apply a high field strength. E (500 kV / cm, or even as high as 600-700 kV / cm), which requires the ceramic to have very high electrical breakdown strength. E b Meanwhile, long-term operation under high electric fields significantly increases the likelihood of increased leakage current within the material, posing a risk of electrical breakdown or even malfunction, thus reducing the material's reliability in practical applications. Furthermore, most microelectronic devices (such as wearable flexible devices and portable power supplies) can typically withstand electric fields of less than 200 kV / cm. Therefore, achieving high saturation polarization intensity (SPI) under low electric fields without sacrificing overall electrical performance is crucial. P s or P max ) and low remanent polarization intensity ( P r Collaboration between these technologies and the development of new high-energy-density dielectric materials is urgent and important, as it not only relates to the working efficiency of dielectric materials but also influences the miniaturization and integration of electronic devices.

[0003] Sodium bismuth titanate (Bi) 0.5 Na 0.5 TiO3 (BNT) is an ABO3-type perovskite ferroelectric material with high... P max (>40 μC / cm) 2 Advantages, but also high P r (~38 μC / cm) 2 This gives it a wide and thick hysteresis loop, causing most of the energy to be dissipated during the discharge process, thus limiting the actual energy that can be obtained. W rec The breakdown field strength is relatively low. Furthermore, pure BNT ceramics also exhibit a breakdown field strength of [missing information].E b Its low dielectric strength and poor dielectric properties severely limit its practical applications. Therefore, technicians utilize (Ba...) 0.3 Sr 0.7 TiO3 was used to dope and modify BNT ceramics to prepare (Bi 0.5 Na 0.5 ) 1-x (Ba 0.3 Sr 0.7 ) x TiO3 ceramics, of which 0.6Bi 0.5 Na 0.5 TiO3-0.4Ba 0.3 Sr 0.7 TiO3 (BNBST) has good overall performance, but its P r The dielectric temperature remains high, and its stability is not good enough. Therefore, how to maintain high dielectric temperature is a key challenge. P max At the same time, reduce P r Obtaining BNBST energy storage ceramic materials with high energy density under low electric fields, improved dielectric temperature stability, and other excellent electrical properties has become an important research topic in the field of energy storage ceramic materials for microelectronic devices. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high energy density Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material under low electric field, specifically targeting (Bi 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 Bi at site A of TiO3 ceramic material 3+ Na + Ba 2+ 、Sr 2+ Ions, using Nd with 12 coordination 3+ Ce 4+ Composition of complex high-valence ions [Nd 0.8 Ce 0.2 ] 3.2+ Doping substitution is performed on Ti at the B site. 4+ Ions, using Co with 6 coordination groups 2+ Al 3+ Mn 4+ Composition of complex low-valence ions [Co 0.2 Al 0.5 Mn 0.3 ] 3.1+Doping and substitution are performed on it in order to maintain high performance through the above-mentioned composite doping modification. P max ,reduce P r This invention aims to improve the effective energy storage density per unit electric field while enhancing dielectric temperature stability, thereby providing a novel, environmentally friendly energy storage ceramic material with excellent comprehensive electrical performance under low electric fields. Another objective of this invention is to provide a method for preparing the aforementioned Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material with high energy storage density under low electric fields, and the resulting product.

[0005] The objective of this invention is achieved through the following technical solution:

[0006] This invention provides a high energy density Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material under low electric field, with Nd having 12 coordination. 3+ Ce 4+ The composite high-valence ion [Nd] 0.8 Ce 0.2 ] 3.2+ Doping and substitution (Bi) 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 Bi at site A in TiO3 3+ Na + Ba 2+ 、Sr 2+ Ions, with Co having 6 coordination sites 2+ Al 3+ Mn 4+ The complex low-valence ion [Co] 0.2 Al 0.5 Mn 0.3 ] 3.1+ Doping and substitution (Bi) 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 Ti at the B site in TiO3 4+ The ions form a chemical formula [(Bi] ] 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 ] 1-1.6x [Nd 0.8 Ce 0.2 ] x Ti 1-y [Co0.2 Al 0.5 Mn 0.3 ] y O3, where 0.015≤x≤0.035, 0.05≤y≤0.08.

[0007] In the above scheme, the ceramic material of the present invention has a breakdown field strength E b ≥200kV / cm; Under an electric field of 200 kV / cm, P max ≥42μC·cm -2 , P r ≤2.0μC·cm -2 Effective energy storage density per unit electric field (per kV) W rec Value) ≥ 0.02 J·cm -3 ·kV -1 Energy storage efficiency η ≥90%; Temperature stability: Dielectric constant within the temperature range of 35~350℃. e r ≥2500, the rate of change of volumetric temperature meets the requirements. TCC 150℃ ≤±15%; Frequency stability: Energy storage density within the frequency range of 1~100Hz. W rec Change rate ≤ 4.5%, energy storage efficiency η Change rate ≤ 2%; Fatigue resistance: 10 cycles 5 After that, energy storage density W rec Change rate ≤2%, energy storage efficiency η Change rate ≤2%; Discharge performance: Time required to release 90% of energy under an electric field of 20–120 kV / cm and a temperature range of 40–140℃. t 0.9 ≤70 ns.

[0008] Another objective of this invention is achieved through the following technical solution:

[0009] The method for preparing the above-mentioned Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material with high energy density under low electric field provided by the present invention includes the following steps:

[0010] (1) Preparation of pre-synthesized precursor powder

[0011] Bi₂O₃, anhydrous Na₂CO₃, BaCO₃, SrCO₃, TiO₂, Nd₂O₃, CeO₂, CoO, Al₂O₃, and MnO₂ were used as raw materials corresponding to Bi, Na, Ba, Sr, Ti, Nd, Ce, Co, Al, and Mn in the general chemical formula. The amount of Bi₂O₃ used was 1.0–1.5 wt% more than the stoichiometric amount in the general chemical formula, while the amounts of the remaining raw materials were the stoichiometric amounts in the general chemical formula. After batching, the materials were ball-milled once using anhydrous ethanol as the ball milling medium. The resulting material was dried, sieved, pressed into shape, and then calcined in a sealed crucible. The calcined material was then ground and sieved to obtain the pre-synthesized precursor powder. The pressing pressure was 5–8 MPa. The calcination process involved heating at 5 °C / min to 840–860 °C and holding at that temperature for 3–5 h.

[0012] (2) Preparation of energy storage ceramic materials

[0013] The pre-synthesized precursor powder is subjected to secondary ball milling. The material obtained after ball milling is dried, ground, sieved, granulated, and aged to obtain a treated material. The treated material is placed in a mold and pressed into shape, and then subjected to debinding heat treatment to obtain a pre-fired part. Finally, the pre-fired part is placed in a zirconia sintering material for sintering. The sintering process is as follows: first, the temperature is raised to 1240-1260℃ at 5℃ / min and held for 10-15 min, then lowered to 1140-1160℃ and held for 3-3.5 h, and then cooled to room temperature in the furnace to obtain the BSBNT-based ceramic material.

[0014] Furthermore, in step (2) of the preparation method of the present invention, the pressing pressure is 6-8 MPa; the glue removal heat treatment is to raise the temperature to 630-650℃ at 1℃ / min and keep it at that temperature for 3-4 h.

[0015] The product was prepared using the above-mentioned method for preparing Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic materials with high energy storage density under low electric field.

[0016] The present invention has the following beneficial effects:

[0017] (1) To obtain BNBST-based energy storage ceramic materials with high energy storage density and good dielectric temperature stability under low electric field, the present invention adopts three measures: ① Using composite ion [Nd 0.8 Ce 0.2 ] 3.2+ Doping and substitution (Bi) 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 Bi in TiO33+ Na + Ba 2+ 、Sr 2+ Ions (written as complex ions: [Bi) 0.3 Na 0.3 Ba 0.12 Sr 0.28 ] 2+ This involves designing to replace low-valence ions with high-valence ions at the A-site, creating cation vacancies, enhancing local structural distortion and domain wall mobility, promoting the increase of micron-scale domain structures, thereby improving polarization intensity and helping to maintain high... P max ② Using composite ions [Co 0.2 Al 0.5 Mn 0.3 ] 3.1+ Doping and substitution (Bi) 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 TiO3 contains Ti 4+ The design involves replacing high-valence ions with low-valence ions at the B-site, promoting the creation of oxygen vacancies. These oxygen vacancies exhibit a pinning effect, hindering domain wall movement, inhibiting domain growth, and promoting the increase of nanoscale domain structures, thereby reducing... P r ③ By controlling the doping amounts at A-site and B-site, and combining this with a two-step sintering method, the grain growth behavior is controlled to obtain ceramic materials with larger and more uniform grain sizes and higher density. Through the synergistic effect of these three measures, a multi-level domain structure design is achieved, thereby enhancing phase transformation stability and improving Δ... P ( P max - P r The goal is to enhance relaxation and obtain BNBST-based energy storage ceramic materials with high energy density and high energy storage efficiency under low electric fields, good temperature, frequency and cycle stability, and excellent charge and discharge performance.

[0018] (2) Breakdown field strength of the Nd / Ce / Co / Al / Mn doped BSBNT-based energy storage ceramic material of the present invention E b With a voltage of ≥200kV / cm, this material exhibits high energy density, excellent temperature stability, frequency stability, fatigue resistance, and discharge performance under low electric fields. It fully meets the application requirements of most microelectronic devices (wearable flexible devices, portable power supplies) and also satisfies the current development needs for miniaturization and integration of electronic products.

[0019] (3) All raw materials of this invention are lead-free, which is environmentally friendly. The burial material used can be reused and the production cost is low. The preparation method does not require expensive equipment, the process is simple and easy to operate, the influencing factors are easy to control, it is suitable for mass production, and it is conducive to promotion and application. Attached Figure Description

[0020] The present invention will now be described in further detail with reference to the embodiments and accompanying drawings:

[0021] Figure 1 These are the XRD phase diagrams of the energy storage ceramic materials in the embodiments and comparative examples of this invention;

[0022] Figure 2 The energy storage ceramic material of Embodiment 1 of the present invention is used at 200 kV / cm. W rec and η Curve showing variation with frequency;

[0023] Figure 3 The energy storage ceramic material of Embodiment 1 of the present invention is tested at 200 kV / cm and 10 Hz. W rec and η Curve showing how the number of cycles changes. Detailed Implementation

[0024] Example 1:

[0025] This embodiment presents a high energy density Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material under low electric field conditions, with the general chemical formula [(Bi 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 ] 0.968 [Nd 0.8 Ce 0.2 ] 0.02 Ti 0.93 [Co 0.2 Al 0.5 Mn 0.3 ] 0.07 O3 is prepared as follows:

[0026] (1) Preparation of pre-synthesized precursor powder

[0027] Bi₂O₃ (99.9% purity), anhydrous Na₂CO₃, BaCO₃, SrCO₃, TiO₂, Nd₂O₃, CeO₂, CoO, Al₂O₃, and MnO₂ were used as raw materials corresponding to Bi, Na, Ba, Sr, Ti, Nd, Ce, Co, Al, and Mn in the above general chemical formulas. The amount of Bi₂O₃ used was 1.0 wt% more than the stoichiometric amount in the general chemical formulas, while the amounts of the other raw materials were the stoichiometric amounts in the general chemical formulas. After batching, anhydrous ethanol was used as the ball milling medium, and the mixture was ball-milled once at 400 r / min for 12 h using a ball:material:anhydrous ethanol ratio of 4:1:3. The resulting material was dried, passed through an 80-mesh sieve, pressed into shape under 6 MPa pressure, placed in a sealed crucible, and calcined at 850℃ in an oxidizing atmosphere at a rate of 5℃ / min for 3.5 hours. h; then the calcined material is ground and passed through a 60-mesh sieve to obtain the pre-synthetic precursor powder;

[0028] (2) Preparation of energy storage ceramic materials

[0029] The pre-synthesized precursor powder was subjected to a second ball milling process (same as the first ball milling process). The material obtained after ball milling was dried, ground, passed through an 80-mesh sieve, granulated (using a 5wt% polyvinyl alcohol aqueous solution as a binder), and aged for 24 hours to obtain a treated material. The treated material was placed in a mold and pressed into small round discs with a thickness of 0.7 mm and a diameter of 13 mm under a pressure of 8 MPa. Then, a debinding heat treatment was performed, i.e., the temperature was increased to 630℃ at 1℃ / min, held for 3.5 hours, and cooled with the furnace to obtain a pre-fired part. Finally, the pre-fired part was placed in a zirconia sintering material for sintering. The sintering process was as follows: the temperature was first increased to 1260℃ at 5℃ / min, held for 10 minutes, then decreased to 1160℃, held for 3.5 hours, and cooled with the furnace to room temperature to obtain the BSBNT-based ceramic material.

[0030] Example 2:

[0031] This embodiment presents a high-energy-density Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material under low electric field and its preparation method, which differs from Embodiment 1 in that:

[0032] 1. The general chemical formula of this embodiment is [(Bi 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 ] 0.96 [Nd 0.8 Ce 0.2 ] 0.025 Ti 0.945[Co 0.2 Al 0.5 Mn 0.3 ] 0.055 O3.

[0033] 2. The calcination temperature in step (1) is 840℃ and the calcination time is 4.5 h.

[0034] 3. The calcination process in step (2) is as follows: first, heat the temperature to 1250℃ at 5℃ / min, hold for 10 min, then lower the temperature to 1160℃, hold for 3 h, and then cool with the furnace.

[0035] Example 3:

[0036] This embodiment presents a high-energy-density Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material under low electric field and its preparation method, which differs from Embodiment 1 in that:

[0037] 1. The general chemical formula of this embodiment is [(Bi 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 ] 0.944 [Nd 0.8 Ce 0.2 ] 0.035 Ti 0.95 [Co 0.2 Al 0.5 Mn 0.3 ] 0.05 O3.

[0038] 2. The calcination temperature in step (1) is 860℃ and the calcination time is 4 h.

[0039] 3. The calcination process in step (2) is as follows: first, heat the temperature to 1250℃ at 5℃ / min, hold for 10 min, then lower the temperature to 1160℃, hold for 3.5 h, and then cool with the furnace.

[0040] Comparative example:

[0041] Based on the general chemical formula [(Bi 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 The TiO3 energy storage ceramic material was used as a comparative example, and its preparation steps were the same as in Example 1.

[0042] The XRD phase diagrams of the energy storage ceramic materials in the embodiments and comparative examples of this invention are as follows: Figure 1 As shown. From Figure 1As can be seen from the data, the diffraction peaks of the energy storage ceramic materials prepared in each embodiment and comparative example are in perfect agreement with the standard spectrum PDF 01-070-9852, indicating that the obtained materials are single-phase Bi. 0.5 Na 0.5 TiO3-based materials.

[0043] The frequency stability and fatigue resistance of Embodiment 1 of the present invention are as follows: Figure 2 , Figure 3 As shown. From Figure 2 It can be seen that the frequency variation of the ceramic sample at 200 kV / cm is in the range of 1–100 Hz. W The rate of change of rec was approximately 4.1%. η The rate of change is approximately 1.9%, indicating that the ceramic material possesses excellent frequency stability. From Figure 3 It can be seen that the ceramic samples, at 200 kV / cm and 10 Hz, have a cycle life ranging from 1 to 10. 5 Within this range W The rate of change of rec was approximately 1.9%. η The rate of change is approximately 2.1%, indicating that the ceramic material has excellent fatigue resistance.

[0044] The performance test results of the energy storage ceramic materials in the embodiments and comparative examples of the present invention are shown in Table 1.

[0045] Table 1 Performance indicators of ceramic materials in the embodiments and comparative examples of the present invention

[0046]

Claims

1. A Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material with high energy storage density under low electric field, characterized in that: With Nd with 12 coordination 3+ Ce 4+ The composite high-valence ion [Nd] 0.8 Ce 0.2 ] 3.2+ Doping and substitution (Bi) 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 Bi at site A in TiO3 3+ Na + Ba 2+ 、Sr 2+ Ions, with Co having 6 coordination sites 2+ Al 3+ Mn 4+ The complex low-valence ion [Co] 0.2 Al 0.5 Mn 0.3 ] 3.1+ Doping and substitution (Bi) 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 Ti at the B site in TiO3 4+ The ions form the general chemical formula [(Bi] ions. 0.5 Na 0.5 ) 0.6 (Ba 0.3 Sr 0.7 ) 0.4 ] 1-1.6x [Nd 0.8 Ce 0.2 ] x Ti 1-y [Co 0.2 Al 0.5 Mn 0.3 ] y O3, where 0.015≤x≤0.035, 0.05≤y≤0.

08.

2. The Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic material with high energy storage density under low electric field according to claim 1, characterized in that: The ceramic material has a breakdown field strength E b ≥200kV / cm; Under an electric field of 200 kV / cm, P max ≥42μC·cm -2 , P r ≤2.0μC·cm -2 Effective energy storage density per unit electric field (per kV) W rec Value) ≥ 0.02 J·cm -3 ·kV -1 Energy storage efficiency η ≥90%; dielectric constant within the temperature range of 35~350℃ e r ≥2500, the rate of change of volumetric temperature meets the requirements. TCC 150℃ ≤±15%; energy storage density in the frequency range of 1~100Hz W rec Change rate ≤ 4.5%, energy storage efficiency η Rate of change ≤ 2%; Cycle 10 5 After that, energy storage density W rec Change rate ≤2%, energy storage efficiency η The rate of change is ≤2%; the time required to release 90% of the energy within an electric field of 20–120 kV / cm and a temperature range of 40–140℃. t 0.9 ≤70 ns.

3. The method for preparing Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic materials with high energy storage density under low electric field as described in claim 1 or 2, characterized in that... Includes the following steps: (1) Preparation of pre-synthesized precursor powder Bi₂O₃, anhydrous Na₂CO₃, BaCO₃, SrCO₃, TiO₂, Nd₂O₃, CeO₂, CoO, Al₂O₃, and MnO₂ were used as raw materials corresponding to Bi, Na, Ba, Sr, Ti, Nd, Ce, Co, Al, and Mn in the general chemical formula. The amount of Bi₂O₃ used was 1.0–1.5 wt% more than the stoichiometric amount in the general chemical formula, while the amounts of the remaining raw materials were the stoichiometric amounts in the general chemical formula. After batching, the materials were ball-milled once using anhydrous ethanol as the ball milling medium. The resulting material was dried, sieved, pressed into shape, and then calcined in a sealed crucible. The calcined material was then ground and sieved to obtain the pre-synthesized precursor powder. The pressing pressure was 5–8 MPa. The calcination process involved heating at 5 °C / min to 840–860 °C and holding at that temperature for 3–5 h. (2) Preparation of energy storage ceramic materials The pre-synthesized precursor powder is subjected to secondary ball milling. The material obtained after ball milling is dried, ground, sieved, granulated, and aged to obtain a treated material. The treated material is placed in a mold and pressed into shape, and then subjected to debinding heat treatment to obtain a pre-fired part. Finally, the pre-fired part is placed in a zirconia sintering material for sintering. The sintering process is as follows: first, the temperature is raised to 1240-1260℃ at 5℃ / min and held for 10-15 min, then lowered to 1140-1160℃ and held for 3-3.5 h, and then cooled to room temperature in the furnace to obtain the BSBNT-based ceramic material.

4. The method for preparing Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic materials with high energy storage density under low electric field according to claim 3, characterized in that: The pressing pressure in step (2) is 6-8 MPa; the glue removal heat treatment is to raise the temperature to 630-650℃ at 1℃ / min and keep it at that temperature for 3-4 hours.

5. The product prepared by the method for preparing Nd / Ce / Co / Al / Mn-doped BSBNT-based ceramic materials with high energy storage density under low electric field as described in claim 3 or 4.